Health in All Policies and intersectorality in Latin America and the Caribbean, 2011 - 2021: a scoping review - Fabio Alberto Escobar Díaz; Zuly Andrea Rodriguez Corredor (Universidad Nacional de Córdoba, 2023)
Introduction: Intersectoriality, since the Alma Ata Conference in 1978, has become a fundamental part of the political discourse on public health, social determinants, and health promotion to address health problems in society. Following the above, it is important to identify the research carried out in Latin America and the Caribbean on this topic in the last decade. Metodology: A scoping review was carried out on the scientific evidence published between 2011 and 2021 in countries of the Latin American region on experiences and intersectoral actions between health and other sectors to address joint public health problems. Results: 15 studies were included; mostly from Brazil, with predominantly qualitative designs and local character. In addition, some analyses highlight the hegemony of the biomedical model, as well as the conflicts and tensions at the ideological level in certain health issues and traditional practices that limit effective intersectoral collaboration. Conclusions: Intersectoriality is not a strictly technical issue, but ideological elements converge that determine its scope and limitations. Studies in countries such as Colombia should be expanded to have evidence that allows an understanding of the barriers and facilitating aspects of intersectorality.